Corporate Risk Disclosure Dynamics in Light of Key Audit Matters Reporting - Qurrota A'yun, Annisa; adi wibowo, Wahyu (Journal Economic Business Innovation, 2025)
Purpose: This paper investigates the association between Key Audit Matters (KAM) disclosures and the level of corporate risk narratives provided in annual reports and the characteristics of the firm, governance structure, and audit quality associated with disclosure practices. Method: The study uses quantitative approach with multiple regression analysis to examine the effect of KAM reporting by its levels of risk disclosures. A content analysis of data extracted from reports was done to study Professional Judgement on the width and depth of risk disclosures based on publicly available corporate reports. Findings: We document a strong positive association between capital market-oriented disclosures and the strength of narrative risk reporting. While firm size, operational complexity, leverage, and profitability significantly increased risk transparency, external auditors' reputation also increased the quality of disclosures. Novelty: This study reveals a new function of KAMs where turning audit report transparency into an effectual mechanism in corporate governance. It builds upon the signaling and agency theory by showing how mandatory audit disclosures are reflective of voluntary narrative reporting behavior. Implications: These findings suggest that, in addition to calls for more transparency in the audit process, there needs to be a greater focus on risk management strategies complementary to these processes. Enhanced disclosure can help companies build trust with the relevant stakeholders and align with global reporting frameworks, while providing regulators and policymakers the important contextual information to help develop appropriate disclosure regulations, including audit requirements. The study aids current deliberations on enhancing the quality of financial reporting and enabling investment decision-making by competitors and others in the market.